2020
DOI: 10.1101/2020.02.21.20026393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in the Availability and Cost of Essential Medicines for Non-Communicable Diseases in Uganda: a descriptive time series analysis

Abstract: Background: Availability of essential medicines for non-communicable diseases (NCDs) is poor in low- and middle-income countries. Availability and cost are conventionally assessed using cross-sectional data. However, these characteristics may vary over time. Methods: We carried out a prospective, descriptive analysis of the availability and cost of essential medicines in 23 Ugandan health facilities over a five-week period. We surveyed facility pharmacies in-person up to five times, recording availability and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…Recent studies have shown different levels of availability of EMHS across health facilities in Uganda. A study by [2] showed higher levels of availability of essential medicines at across all levels of care than those observed in this study. However, the results are from a sample of 23 health facilities.…”
Section: Discussioncontrasting
confidence: 62%
“…Recent studies have shown different levels of availability of EMHS across health facilities in Uganda. A study by [2] showed higher levels of availability of essential medicines at across all levels of care than those observed in this study. However, the results are from a sample of 23 health facilities.…”
Section: Discussioncontrasting
confidence: 62%
“…Other EDL barriers were poor geographical access contributing to limited access to essential in vitro diagnostics in rural areas 96 , and limited health facility access: availability of essential in vitro diagnostics at referral hospitals but not primary health care facilities 96 and public facilities 98 , and poorly resourced health facilities 97 . The barriers for the implementation of the EML are similar to the EDL barriers reported above, and the main barriers were poor financial access 39, 48, 78, 79, 83, 86–89, 104, 110, 136, 140–149 , poor geographical access 36, 65, 74, 82, 104, 143, 146, 150 and health facility access 73, 74, 106, 150152 .…”
Section: Resultssupporting
confidence: 54%
“…Similar and other related barriers were also cited in the EML implementation. The main barriers unique to the EML included inefficient procurement processes 34, 47, 49, 63, 65, 69, 70, 82, 157 , poor stock management practices 39, 49, 50, 53, 94, 105, 107, 140, 158, 159 , and inefficient distribution systems 40, 49, 75, 94, 111, 131, 146, 160, 161 .…”
Section: Resultsmentioning
confidence: 99%
“…A large population and inadequate pharmaceutical budgets have perpetually combined with human resource and technological inadequacies in medicines management to simultaneously exacerbate the frequent stock-out of essential medicines. 39,40 Stock-outs of medicines and limited health commodities are a primer to AMR because they perpetuate missed, incomplete and inappropriate doses, as well as depriving prescribers of diagnostic tools, leading to an overreliance on empirical diagnoses and management of infections. Additionally, stock-outs drive patients from public sector health services to the private health market, where profit-motivated practices compromise adherence to treatment guidelines and appropriate medicines use.…”
Section: Threats To Sustainable Medicines Usementioning
confidence: 99%